Application of uniportal video-assisted thoracic surgery (VATS) in pulmonary tumors - Zhao, Xiaopeng; Yu, Fan; Wang, Miao; Zhang, Haoran; Wang, Hongyan (Journal of Thoracic Disease; Vol 11, No 1 (January 26, 2019): Journal of Thoracic Disease, 2018)
At present, lung cancer resection can be done by different approaches and methods, such as traditional thoracotomy, small incision thoracotomy, thoracoscopic surgery and robot surgery. Video-assisted thoracic surgery (VATS) lung cancer resection greatly reduces the trauma of traditional thoracotomy, and has obvious advantages in terms of hospital stay, complication rate, survival time and so on (1,2).